(untitled) (Perioperaciina Medicina, 2021)
Background: High mortality because of various infectious complications (immediate cause in 42.5 % of cases), the ever-increasing frequency of purulent inflammatory diseases, as well as the growth of microbial resistance to anti-bacterial drugs, force to seek a solution to the problem among local antiseptics. Aim: to compare the effectiveness of antiseptics DECASAN Yuria-Pharm and CUTASEPT G in the treatment of puru-lent inflammatory diseases of different localization. Materials and methods: The study involved 30 patients with purulent inflammatory diseases of various localiza-tions. Patients were divided into two groups, according to the chosen tactics of local antiseptic therapy, in patients of the first study group (n = 15; mean age – 49.73 ± 6.35 years) antiseptic treatment was performed with a drug based on 0.02 % decamethoxine (Decasan). In the second group (n = 15; mean age – 51.4 ± 5.14 years) treatment was performed with a disinfectant (skin antiseptic) “Cutasept G”. Collection of material for microbiological examination (bacteriological culture) was performed before treatment, 3 and 5 days after treatment. Probability analysis was performed according to Student’s t-test. A statistically significant difference between the indicators was considered when the probability of validity of the null hypothesis was less than 5 % (p <0.05). Results: Analyzing the results of bacteriological examination of both groups, in the first, where Decasan was used and in the second, with the use of Cutasept G, it was found that at the beginning of treatment there was a pronounced microbial colonization of wounds, not significantly different among patients in both groups (p <0.05). Microbio-logical observation of the course of purulent-inflammatory process in the dynamics showed a significantly slowed down process of microbial purification in the second group (Cutasept G), the condition for 5 days was lg (8.8 ± 0.4) CFU/ml. At that time for patients of the first comparison group the number of microorganisms in 1 ml of wound contents, expressed in lg, was (4.8 ± 0.4) CFU/ml, which does not exceed the critical level. The obtained values were significantly higher than with Cutasept G (p <0.05), which was twice higher than the level of microbial colonization compared to the treatment of wounds with 0.02 % decamethoxine solution (p <0.001). Conclusions: The use of antiseptic 0.02 % decamethoxine for 5 days provides a reduction in the number of oppor-tunistic pathogens lg (4.8 ± 0.4) CFU/ml, which is 1.9 times lower (p <0.05) compared with the use of Cutasept G, creating conditions for the settlement of normal microbiotic skin (Corynebacterium spp., S. epidermidis). Antiseptic Dekasan is characterized by good healing properties due to its high antimicrobial activity, isotonicity, which makes it possible to use it successfully in patients with purulent inflammatory diseases of various localizations. In addition, the use of Dekasan promotes rapid cleansing of wounds from purulent-necrotic contents and formation of granula-tion tissue in them.